Extraction and characterization of collagen and gelatin from body wall of sea cucumbers Stichopus horrens and Holothuria arenicola - Barzkar,Noora; Attaran-Fariman,Gilan; Taheri,Ali; Venmathi Maran,Balu Alagar (PeerJ, 2024)
Background Marine invertebrates, including sponges, molluscs, jellyfish, mussels, and sea cucumbers, are abundant sources of high-quality collagen and offer advantages such as availability, ease of processing, lower inflammatory response, and good metabolic compatibility. Approximately 70% of the total protein in the body wall of sea cucumbers is collagen. Gelatin is a water-soluble protein produced from heat-denatured collagen and has various industrial applications. Methods Pepsin-solubilized collagen was extracted from the body wall of two sea cucumber Stichopus horrens and Holothuria arenicola, species found in the Oman Sea and characterized with SDS-PAGE and amino acid composition. Then gelatin was extracted from pepsin-solubilized collagen of S. horrens and some rheological properties were measured. Results Amino acid composition and SDS-PAGE analysis showed that the collagen from both species was type I, with one α1 chain and β chains, with molecular weights of 125 and 250 kDa, respectively. Glycine was the most abundant amino acid in the collagen from both sea cucumber species. The pepsin-soluble collagens from both species had high levels of glycine, proline, alanine, glutamic acid, and hydroxyproline. The gelatin from S. horrens had a melting point of 30 °C and displayed exceptional thermal stability, surpassing that of mammalian gelatin. Its gelling point was 5 °C, like that of cold-water fish gelatin, with a viscosity of 2.065 cp-lower than mammal gelatins. These findings suggested that collagen and gelatin from sea cucumbers could be useful in nutraceutical, pharmaceutical and cosmetic industries.
Keywords: Pepsin-solubilized collagen; Gelatin; Sea cucumber; Stichopus horrens; Holothuria arenicola